(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For the past few years, there has been an air of pessimism in the market about the real estate sector. There are various reasons which have affected the growth of the sector negatively. The recent announcement of the Real Estate Regulator Bill (RERA) which was passed by the Indian Parliament in March 2016 has ushered a new era in the Indian property market. This bill lays the groundwork for a more accountable and transparent system in construction and buying and selling of properties. This also provides the much needed cheer and hope for both buyers and investors.